Guarda-tombo: o inventário da queda ou uma escrita-experiência do corpo pe(n)sante - Campos Neto, José Danilo Rodrigues (2023)
This research unfolds as a performative writing project I have called “experiencewriting”. Emerging from (and attending to) the act of falling - literally and metaphorically - this writing is composed by the circumstances with which the author’s body is entangled in the present, while also meeting past experiences. In this respect, this thesis is fully processual and aligns itself to the proposition of a “performative research” (HASEMAN, 2006). Guided by intuition and an enthusiasm of practice (HASEMAN, 2006), it assembles a collection of terms and images that results from the polysemic wordplay related to the act of falling, including dance and performance art pieces that explore the concept of falling. Drawing clues from these artworks in the text produces considerations about the concept of presence — weak, strong and radical (FISCHERLICHTE, 2012) — and rehearses the ways in which these qualities become materialized. Reflecting upon subjects such as weight, falling, qualities of performative presence, as they fuel a critical writing in the Arts, connects everyday life to the act of writing and frames the body in terms of a weighting-thinking state (BARDET, 2014). In such experience-writing, a few artworks are brought into the larger discussion about falling and fallen bodies. These include some of my own works as well as other artists’, such as Yves Klein, Bas Jan Ader, and Trisha Brown. The theoretical discussion seeks consistency in the concepts of “falling” in relation to creative processes in dance (POPPE, 2018), of “becoming”, and “body memory” (ROCHA, 2016; ROLNIK, 1993), all of which contribute to the discussion about the constitutive elements of artworks, about how these might advance modes of critical thinking, and how these resonate in the current writing of this thesis. Towards the end, I present a series of falls, of different natures and perspectives, as practical propositions emerging from the investigation of weight, with which the readers can also attune themselves, as they are invited to connect their own weight with the weight of the spaces they are in, and to collect their own stumbles and falls, be these understood as dance or as writing.